ABDOMINAL POLYLYMPHADENOPATHY DUE TO SARCOIDOSIS - Hülya ÇETİNKAYA and Kadir BAHAR and Kubilay ÇINAR and Bülent MIZRAK and Ahmet C. KAUR and Cihan YURDAYDIN and Cemil EKİNCİ and Nurdan TÖZÜN and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-